Modeling of the elastic mechanical behavior of thin compliant joints under load for highest-precision applications - Torres Melgarejo, Mario André (Pontificia Universidad Católica del Perú, 2018)
For the most demanding measurement tasks in force metrology flexure hinges in compliant mechanisms represent a key component. To enhance the mechanical properties of devices like weighing cells, the ability of precise modeling of flexure hinges is essential. The present scientific work focuses on the modeling of the mechanical behavior of a single flexure hinge subjected to geometric deviations and non-ideal loading conditions as those encountered in weighing cells. The considered hinge has a semi-circular contour and a large width compared to its minimum notch height. This geometry is modeled using the finite element method. Requirements for a trustworthy and efficient computation are elaborated under the consideration of geometric deviations for later parametric studies. Analytical expressions found in the literature are compared to numerical results to prove the validity of their assumptions for thin hinges. The model is used for studying the deviation of the stiffness in non-ideal flexure hinges. Sources of deviation are identified and described by parameters. The range of values for each parameter is chosen on the basis of available manufacturing technology. Influential parameters are identified through a sensitivity analysis. The effect of loading conditions is studied in the context of the application in weighing cells. For the enhancement of the overall sensitivity, the stiffness of the flexure hinges can be reduced. One option, the alteration of the geometry by adding a flexure strip in the center of the semi-circular flexure hinge is studied in comparison to existing analytical equations. The effects of ground tilts for a single loaded flexure hinge are investigated as a foundation for future modeling of a tilt insensitive state of a weighing cell mechanism (autostatic state). By adjusting the vertical position of the center of mass of the lever, the tilt sensitivity can be reduced to zero. An approach to find the position for this state is presented considering the numerical limitations of finite element modeling. Using this approach, the variation of the sought position is evaluated for different values of the design parameters.
Keywords: Estructuras metálicas--Uniones; Método de elementos finitos; https://purl.org/pe-repo/ocde/ford#2.03.01